1990
DOI: 10.1002/ijc.2910460114
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modification of multi‐drug resistance (mdr) in vitro detected by a novel fluorometric microculture cytotoxicity assay. Reversal of resistance and selective cytotoxic actions of cyclosporin a and verapamil on mdr leukemia t‐cells

Abstract: A novel fluorometric microculture cytotoxicity assay (FMCA), based on measurements of fluorescein diacetate (FDA) hydrolysis and DNA staining by Hoechst 33342, was used for drug sensitivity testing and detection of resistance reversal in acute lymphoblastic leukemia (ALL) cell lines. The 72-hr assay was found to be sensitive, reproducible and linearly related to the number of viable cells within a broad range of cell concentrations. At clinically achievable drug concentrations, the calcium channel blocker Vera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Empirically derived cut-off concentrations (EDCC) were selected according to principles described previously and are in most cases in the range achievable in plasma (Larsson et al, 1992a). EDCC concentrations of each drug were used in the combinations (Table II) Table I. FMCA procedure The principal steps of the assay procedure have been described previously (Larsson et al, 1992a;Larsson & Nygren, 1990). Day 1 180 pl of the leukaemia preparation at 2.5-5 x 10' cells ml-' in culture medium were seeded into the wells of V-shaped 96 well experimental microtiter plates (Nunc, Roskilde, Denmark) prepared as described above.…”
Section: Reagents and Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically derived cut-off concentrations (EDCC) were selected according to principles described previously and are in most cases in the range achievable in plasma (Larsson et al, 1992a). EDCC concentrations of each drug were used in the combinations (Table II) Table I. FMCA procedure The principal steps of the assay procedure have been described previously (Larsson et al, 1992a;Larsson & Nygren, 1990). Day 1 180 pl of the leukaemia preparation at 2.5-5 x 10' cells ml-' in culture medium were seeded into the wells of V-shaped 96 well experimental microtiter plates (Nunc, Roskilde, Denmark) prepared as described above.…”
Section: Reagents and Drugsmentioning
confidence: 99%
“…We have previously described the fluorometric microculture cytotoxicity assay (FMCA) for drug sensitivity testing of cell lines and tumour cell samples from patients with acute myelocytic leukaemia (AML; Larsson et al, 1992a;Larsson & Nygren, 1990). In the present study we employed this method for the study of drug interactions in AML.…”
mentioning
confidence: 99%
“…It has therefore been suggested that in vitro testing may be a valuable tool in the preclinical evaluation of new anticancer agents (23,24). In the present study we have employed a fluorometric assay based on detection of esterase activity in cells with intact plasma membranes (16). Indeed, this assay system has been found to give promising individual clinical correlations ( 18).…”
Section: Discussionmentioning
confidence: 99%
“…The histocytic lymphoma cell line U-937 (15) was used as a TNF-(r and IFN-y sensitive control. Cell survival after culture in the presence and absence of cytokines was determined by using the fluorometric microculture cytotoxicity assay (FMCA) as described elsewhere (16). The assay is based on hydrolysis of non-fluorescent fluorescein diacetate (FDA; Sigma Chem.…”
Section: Measurement Of Cytokine Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation